0=-67.8558Q(-0.8239+0.0021Q)

Rewrite the equation as -67.8558Q(-0.8239+0.0021Q)=0.

-67.8558Q(-0.8239+0.0021Q)=0

Divide each term in -67.8558Q(-0.8239+0.0021Q)=0 by -67.8558.

-67.8558Q(-0.8239+0.0021Q)-67.8558=0-67.8558

Cancel the common factor.

-67.8558Q(-0.8239+0.0021Q)-67.8558=0-67.8558

Divide Q(-0.8239+0.0021Q) by 1.

Q(-0.8239+0.0021Q)=0-67.8558

Q(-0.8239+0.0021Q)=0-67.8558

Divide 0 by -67.8558.

Q(-0.8239+0.0021Q)=0

If any individual factor on the left side of the equation is equal to 0, the entire expression will be equal to 0.

Q=0

-0.8239+0.0021Q=0

Set the first factor equal to 0.

Q=0

Set the next factor equal to 0.

-0.8239+0.0021Q=0

Add 0.8239 to both sides of the equation.

0.0021Q=0.8239

Divide each term by 0.0021 and simplify.

Divide each term in 0.0021Q=0.8239 by 0.0021.

0.0021Q0.0021=0.82390.0021

Cancel the common factor of 0.0021.

Q=0.82390.0021

Divide 0.8239 by 0.0021.

Q=392.3‾

Q=392.3‾

Q=392.3‾

The final solution is all the values that make -67.8558Q(-0.8239+0.0021Q)-67.8558=0-67.8558 true.

Q=0,392.3‾

Solve for Q 0=-67.8558Q(-0.8239+0.0021Q)